Dynamic Control of Foraging Behavior by the Habenulo-Raphe Pathway - Dheer, Amarpreet (Université d'Ottawa / University of Ottawa, 2025)
The dorsal raphe nucleus (DRN) in the midbrain is a hub-like network receiving substantial afferent connections and providing widespread efferent connections to the brain. This network architecture makes serotonin (5-HT, 5-hydroxytryptamine) neurons in the DRN well positioned to broadcast unified, ethologically salient signals to influence behavior. Among the many inputs to the DRN are long-range glutamatergic projections from the lateral habenula (LHb). While the LHb is known to be involved in punishment, avoidance, and negative valence processing, how its input to the DRN regulates aspects of adaptive decision-making remains unclear. In this study, we investigate how the LHb-DRN pathway influences decision-making using a novel spatial navigation paradigm, the Hidden Food Maze (HFM). By expressing ChrimsonR in the LHb, we selectively stimulated glutamatergic axons from the LHb located in the DRN after mice had learned the location of a hidden reward in the HFM. Our findings show that high-frequency stimulation (20Hz) rapidly and robustly disrupts the navigational strategy used by the animals. Specifically, the stimulation induces longer travel paths, alters hole-checking behavior, increases angular deviations from optimal trajectories, but does not affect movement speed. The nature of these disruptions is consistent with the hypothesis that LHb-DRN activation triggers a stable state transition from exploitation to exploration. These results suggest that the LHb-DRN pathway plays a critical role in behavioral flexibility by dynamically modulating behavioral state transitions during decision-making.
Keywords: Decision-making; exploitation; exploration; serotonin; dorsal raphe nucleus; habenula